Studi Perbandingan Emisi dan Kinerja Motor Bensin dengan Bahan Bakar Campuran Etanol - Pratama, Mahardhika Putra; Novianto, Arief (Jurnal Teknik Mesin, 2025)
The rapid development of transportation can have an impact on the surrounding environment such as congestion, air pollution, noise pollution, accidents, delays, and increased fuel consumption. Alternative fuels are very necessary and needed to minimize the dangers of the impact of increased motorized vehicles, especially air pollution and increased fuel consumption. Ethanol is one of the alternative fuel sources to replace or as a fuel mixture that is classified as biofuel. The purpose of this study is to determine the impact of ethanol-blend use on exhaust emissions and engine performance in gasoline motorcycles. The ethanol-blend variations used as fuel start from pure pertalite (PE0), pertalite + 5% ethanol (PE5), pertalite + 10% ethanol (PE10), pertalite + 15% ethanol (PE15), and pertalite + 20% ethanol (PE20). The results of this study show that the use of ethanol-blend has an impact on engine performance and exhaust emissions of gasoline motorcycles. PE5 fuel is the best fuel variation with CO exhaust emissions of 0.13% and HC of 26.7 ppm at 4000 rpm engine speed. Meanwhile, the highest torque engine performance was achieved with PE5 fuel with a torque of 114.9 Nm, and the engine power reached 71.6 HP with PE20 fuel. Compared to the use of pure pertalite fuel of 113.6 Nm at 2500 rpm engine speed and 69.0 HP at 5000 rpm engine speed, respectively.